2023
DOI: 10.1021/acs.energyfuels.3c01267
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Shale Gas-Bearing Properties Based on Carbon Isotope Fractionation Model: A Case Study from Longmaxi Formation Shales in Jiaoshiba Area, Sichuan Basin, China

Abstract: Adsorbed gas ratio and gas-in-place (GIP) content are two critical parameters for determining shale gas resources and devising development plans. Existing traditional methods have their limitations in solving the above issues, while a novel approach for evaluating the aforementioned key parameters was provided by the carbon isotope fractionation (CIF) model. To investigate the stable carbon isotope fractionation and shale gas content characteristics during the degassing process, 10 shale samples from Well JY A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…On this basis, Li developed an isotope fractionation model considering multiscale and multimechanism coupling, in which the gas equation of state was used for the differential pressure seepage of free gas in fractures, the one-dimensional continuous flow equation coupling diffusion and adsorption/desorption was used for the gas flow in matrix pores, and Fick’s second law was used for the diffusion of dissolved gases in the kerogen pores . This model has been initially applied in Fuling , and Luzhou blocks , in the Sichuan Basin, and good evaluation results have been obtained, and it has been verified by pressure-preserving coring. The accuracy of this model in evaluating the in situ gas content parameters is better than the traditional USBM method, polynomial fitting method, and Amoco method.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On this basis, Li developed an isotope fractionation model considering multiscale and multimechanism coupling, in which the gas equation of state was used for the differential pressure seepage of free gas in fractures, the one-dimensional continuous flow equation coupling diffusion and adsorption/desorption was used for the gas flow in matrix pores, and Fick’s second law was used for the diffusion of dissolved gases in the kerogen pores . This model has been initially applied in Fuling , and Luzhou blocks , in the Sichuan Basin, and good evaluation results have been obtained, and it has been verified by pressure-preserving coring. The accuracy of this model in evaluating the in situ gas content parameters is better than the traditional USBM method, polynomial fitting method, and Amoco method.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have found significant isotopic fractionation during gas desorption from shale and coal beds. The latter further clarified the isotope fractionation characteristics during desorption and revealed the mechanism of isotope fractionation and found that the isotope fractionation characteristics of shale gas desorption were closely correlated with the shale’s composition, physical properties, and gas-bearing properties. Li et al used this as an entry point to develop a set of carbon isotope fractionation (CIF) models for evaluating gas content according to different gas flow mechanisms by calibrating the amount of desorbed gas and isotope values. This model has now been preliminarily applied in Jiaoshiba , and Luzhou shale gas block , in the Sichuan Basin and has achieved better evaluation results, but the applicability and accuracy of this method in normal-pressure shale gas have yet to be verified. Especially, there is a lack of systematic research on analyzing and comparing the evaluation results of gas-bearing parameters in normal-pressure shale reservoirs using multiple methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation